Escherichia coli “TatExpress” strains export several g/L human growth hormone to the periplasm by the Tat pathway - Guerrero Montero, Isabel (Biotechnol Bioeng, 2019)
Escherichia coli is a heavily used platform for the production of biotherapeutic and other high‐value proteins, and a favored strategy is to export the protein of interest to the periplasm to simplify downstream processing and facilitate disulfide bond formation. The Sec pathway is the standard means of transporting the target protein but it is unable to transport complex or rapidly folding proteins because the Sec system can only transport proteins in an unfolded state. The Tat system also operates to transport proteins to the periplasm, and it has significant potential as an alternative means of recombinant protein production because it transports fully folded proteins. Here, we have tested the Tat system's full potential for the production of biotherapeutics for the first time using fed‐batch fermentation. We expressed human growth hormone (hGH) with a Tat signal peptide in E. coli W3110 “TatExpress” strains that contain elevated levels of the Tat apparatus. This construct contained four amino acids from TorA at the hGH N‐terminus as well as the initiation methionine from hGH, which is removed in vivo. We show that the protein is efficiently exported to the periplasm during extended fed‐batch fermentation, to the extent that it is by far the most abundant protein in the periplasm. The protein was shown to be homogeneous, disulfide bonded, and active. The bioassay showed that the yields of purified periplasmic hGH are 5.4 g/L culture whereas an enzyme‐linked immunosorbent assay gave a figure of 2.39 g/L. Separate analysis of a TorA signal peptide linked to hGH construct lacking any additional amino acids likewise showed efficient export to the periplasm, although yields were approximately two‐fold lower.